Development of blood transfusion external quality assessment program at national scale - Chuong Van Le; Nguyen Nhat Tran; Van Thi Kim Nguyen; Nhu Le Thao Bui; Thu Thi Thanh Do; Phuc Thi Diem Huynh (Revista Cubana de Medicina Militar)
Introduction: External quality assessment is a crucial component in ensuring the quality of blood transfusion testing laboratories. Objectives: To develop a procedure for generating external quality assessment items for blood transfusion testing to evaluate participants' performance. Methods: Experimental research was conducted at Quality Control Center for Medical laboratory- University of Medicine and Pharmacy at Ho Chi Minh City, Vietnam. Three items, including red blood cell, serum, and atypical antibody serum samples, were assessed for homogeneity and stability; 5 assessment areas, including ABO grouping, Rh grouping, compatible cross matches, Coombs test, and screening of atypical antibodies, were utilized to evaluate the performance of 38 participants in the 2020-2021 period. Results: Red blood cell and serum samples maintained quality for a specific period at controlled temperatures, while serum samples with atypical antibodies showed stability at different temperatures. The participants demonstrated high satisfactory performance in ABO grouping, Rh grouping, Coombs test, and screening for atypical antibodies. However, the most unsatisfactory performance was reported in crossmatching, with 15% of participants unsatisfactory results. Conclusion: The procedure of production of proficiency testing items has been successfully developed, and its application at the national level is suggested to improve the quality of blood transfusion laboratories.